Hubungan Perilaku Caring Perawat Dengan Tingkat Kepuasan Pasien Saat Pandemi Covid -19 Di Salah Satu Rumah Sakit Swasta Yogyakarta - Kris Mulyaningsih, Rini; Wardani, Yulia; Suparmi CB, Sr. Lucilla (STIKes Panti Rapih, 2022)
Background: Covid-19 has becoming a global non-natural pandemic since January 30, 2020, and expanding rapidly throughout the world. Covid-19 is a respiratory infection caused by the SARS Cov-2 virus that has never been found in humans and attacks respiratory system with symptoms of fever, cough, and shortness of breath. The increasment of Covid-19 cases at hospital affects the quality of nursing care. This affects the caring behaviour of nurses and the quality of service in determining patient satisfaction, especially during a pandemic. Objective: To determine the relationship between nurses, caring behaviour and the level of patient satisfaction during the Covid-19 pandemic at the inpatient room of the private hospitals in Yogyakarta. Key words: covid-19, caring, patient satisfaction